Electromagnetic energy transfer in the atmosphere ionized by laser radiation - Balandin, S. F.; Donchenko, Valeriy A.; Myshkin, V. F.; Potekaev, Aleksandr I. 1951-; Khan, V. A.; Abramova, E. S. (Russian physics journal)
The physical processes occurring in the atmosphere, when weak ionization channels are formed by laser radiation, are discussed. An electromagnetic energy transmission scheme is proposed and the parameters necessary for its technical implementation are calculated. A variant of the electromagnetic energy transmission using a 'plasma mirror' in the atmosphere is considered. The laser pulse frequencies, durations, and energies, at which a weak ionization channel is formed in the atmosphere and ionosphere, are estimated.